2013
DOI: 10.1111/bju.12204
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary management of renal cell carcinoma (RCC) in Victoria: implications for longer term outcomes and costs

Abstract: indicates that both authors contributed equally to this paper. Objective• To describe the contemporary patterns of care for renal cell carcinoma (RCC) using a whole of population series from Victoria. Patients and methods• Retrospective review of medical records of all patients diagnosed and treated for RCC in Victoria in 2009. • Patients were identified via the State-wide Victorian CancerRegistry.• Patient demographic characteristics, symptoms, stage, and first-line treatment were assessed.• Associations betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…The optimization of the disease management should be based on clinical trials but also on real experiences (Schmidinger et al, 2013). Such registries, also known as “real world” or “real life” studies, providing insights into treatment patterns and outcomes, are emerging as a crucial tool for the clinicians because of a major reproducibility compared with randomized trials (Shek et al, 2012; Ta et al, 2013; Vaishampayan et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…The optimization of the disease management should be based on clinical trials but also on real experiences (Schmidinger et al, 2013). Such registries, also known as “real world” or “real life” studies, providing insights into treatment patterns and outcomes, are emerging as a crucial tool for the clinicians because of a major reproducibility compared with randomized trials (Shek et al, 2012; Ta et al, 2013; Vaishampayan et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in Australia have demonstrated that less technically difficult procedures with equivalent efficacy for oncological control are favored in rural settings, for example, total mastectomy was more common in rural hospitals than breast‐sparing surgery for breast cancer; and in lower volume settings, where permanent colostomy was more common than temporary ileostomy for stoma creation during colorectal cancer management . Previous studies from Victoria have demonstrated that PN rates were lower in rural areas compared with metropolitan, and a population‐based study of all kidney cancer patients managed in New South Wales between 2001 and 2009 identified that a caseload of >8 cases/year increased the likelihood of receiving PN (OR: 2.4, 95%CI: 1.5‐3.8) . Further, in direct parallel with our findings, a large multicenter retrospective study of 913 patients who underwent surgical management for localized renal masses in the USA demonstrated that centers with >20 cases/year had a higher rate of PN than lower‐volume centers, which was associated with better postoperative kidney function …”
Section: Discussionmentioning
confidence: 99%
“…3,4 Accordingly, more than 65% of lesions are localized to the kidney at diagnosis. 3,5 Patients managed surgically for T1a RCC (localized tumors ≤4 cm) have an excellent prognosis, with 10-year survival as high as 93% in some studies. 6 Considering the excellent survival times for patients managed with T1a RCC, concerns have arisen over adverse sequelae of renal parenchymal resection, particularly the potential for iatrogenic chronic kidney disease (CKD).…”
Section: Introductionmentioning
confidence: 99%
“…A population‐based study examining the treatment of RCC in Australia's most populous state, New South Wales, found that the use of NSS for localized RCC increased from 11% to 23% between 2001 and 2009 . Unfortunately, this paper did not report data for T1a and T1b tumours separately; however, a population‐based study from Australia's second most populated state, Victoria, reported that 27% of all T1 tumours and 39% of T1a tumours were treated by NSS in 2009 . This study also found that NSS for T1a tumours was less likely for patients residing in regional (26%) than metropolitan (43%) areas.…”
Section: Introductionmentioning
confidence: 99%